2013
DOI: 10.1007/s00464-013-2829-3
|View full text |Cite
|
Sign up to set email alerts
|

Does Roux-en-Y gastrectomy for gastric cancer influence glucose homeostasis in lean patients?

Abstract: Diabetes response was confirmed, however with more refractory cases than in bariatric controls, whereas high proportions of NOD occurred. Such dichotomous pattern seems unusual albeit consistent with previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…However, our finding was similar to that of a previous report, which found that 37.5% of lean patients with GC had improved glucose metabolism [11]. The low rate of DM remission in the patients with GC after TG may be associated with (1) less enteral bypass, (2) relatively lean body composition of patients with GC compared with morbidly obese ones, and 3) further anticancer therapy affecting glucose metabolism in post-TG cases.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, our finding was similar to that of a previous report, which found that 37.5% of lean patients with GC had improved glucose metabolism [11]. The low rate of DM remission in the patients with GC after TG may be associated with (1) less enteral bypass, (2) relatively lean body composition of patients with GC compared with morbidly obese ones, and 3) further anticancer therapy affecting glucose metabolism in post-TG cases.…”
Section: Discussionsupporting
confidence: 85%
“…Another http://dx.doi.org/10.1016/j.soard.2015. 11.024 1550-7289/ r 2015 American Society for Metabolic and Bariatric Surgery. All rights reserved.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Gastrectomy to treat gastric cancer is technically similar to bariatric surgery; therefore, it was expected to have metabolic benefits in gastric cancer patients with T2DM. Several studies have discussed improvement in glycemic control and weight reduction after gastrectomy in gastric cancer patients [15][16][17][18]28,29]. However, no studies have compared gastrectomy to non-surgical treatment in gastric cancer patients, except for our previous epidemiological study [18].…”
Section: Discussionmentioning
confidence: 97%
“…Finally, Hayashi SY et al . reported a high rate of refractory cases in diabetic and gastric cancer patients, and also high rate of new-onset diabetes cases in non-diabetic and gastric cancer patients, following roux-en-y gastrectomy 21 . Our study similarly demonstrated that EDNG (total gastrectomy) resulted in lower insulin, higher glucagon and subsequently inferior glucose control level when compared to EDG (bypassed and preserved stomach).…”
Section: Discussionmentioning
confidence: 99%